“Canne di piombo ascose”. Tecniche geomatiche per un nuovo rilievo della grotta degli Animali della villa medicea di Castello - Tucci, Grazia; Conti, Alessandro; Fiorini, Lidia (Opus Incertum, 2019)
In the past, the need to exhaustively document the gardens and artificial grottoes collided with the difficulty to survey and render their organic geometries. Also because of this reason, restoration Charters tended to overlook the issue of survey. The current geomatic techniques, through high resolution sampling, allow the acquiring of realistic and correct representations, also from a metric point of view. However, the use of digital models derived from automatic measuring tools does not guarantee their quality. This can be validated by strict control of the procedures and by means of metadata, i.e. the information describing the data and how they are obtained. The new survey contributed to the knowledge of the historical hydraulic system and its restoration and suggests that drawing A 1640v refers to the state before installation of the cladding. Future research will examine the narrow tunnels in the retaining wall around the grotto.